THE IMPACT OF NATURE OF INDUSTRY, FINANCIAL TARGET AND STABILITY ON FINANCIAL STATEMENT FRAUD - Citra Setyowati; Hetty Muniroh (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Financial statement fraud is defined by the useful omission or fraud of a specific amount in a financial report in order to deceive those who use financial statements. The objective of this research is show how industry situation, financial objectives, and financial stability affect fraudulent financial reporting in food and beverage firms listed on the Indonesia Stock Exchange (IDX) to 2019 to 2021. Financial statement fraud is the dependent variable in this research. Financial stability, financial targets and industrial conditions are independent variables. Purposive sampling, namely a sampling method combined with documentation, is the data collection methodology used in this research. The research sample consisted of 14 companies, so the total observations were 42. To obtain the best unbiased linear estimation (BLUE) data, the multiple linear analysis technique used in this research had previously been tested with classic assumptions in SPSS 22. This research explains that fraud is influenced by not significantly positive by financial stability and financial targets, but not significantly influenced negatively by industrial conditions.